Longitudinal assessment of the prevalence of Fusobacterium necrophorum, Fusobacterium varium, and Salmonella enterica in the nasal cavity, ruminal fluid, and feces of finishing beef steers with and without liver abscesses - Dornbach, Colten W.; Broadway, Paul R.; Wells, James E.; Childress, Kallie D.; Thompson-Smith, Aubrey C.; Canterbury, Landon G.; Burdick Sanchez, Nicole C.; Mathieu, Jacque; Schwarz, Cory; Laverde Gomez, Jenny; Tikhonova, Marina; Nagaraja, T. G.; et al. (Frontiers in Microbiology, 2025)
The objective was to longitudinally assess the prevalence of F. necrophorum subsp. necrophorum, F. necrophorum subsp. funduliforme, F. varium, and Salmonella enterica in the nasal cavity, ruminal fluid, and feces of finishing beef steers with and without LA. Crossbred steers (n = 225; 353 ± 39.6 kg) were transported to a feedlot and fed a high-concentrate diet. Nasal, ruminal fluid, and fecal samples were collected following feedlot arrival (d 5), 1 week after adaptation to a finishing diet (d 35), and the day before harvest (study end). Livers were collected at harvest and examined for LA, and cattle were subsequently assigned into either control or liver abscess groups. Overall LA prevalence was 18.7%. The concentration and prevalence of Salmonella decreased in ruminal fluid and increased in feces with days on feed (p < 0.01). Conversely, ruminal fluid prevalence of F. necrophorum subsp. necrophorum and F. varium increased with days on feed (p < 0.01). Fusobacterium abundance in ruminal fluid and feces was not indicative of LA development except for F. varium being more abundant in the ruminal fluid of steers with LA (p < 0.01). Abundance of F. necrophorum subsp. necrophorum was greater in abscessed liver tissue than healthy tissue (p = 0.03), although no other differences in bacterial abundance or prevalence were observed in livers. Overall, Fusobacterium and Salmonella prevalence in the nasal cavity, ruminal fluid, and feces were affected by days on feed, but their prevalence and abundance were not indicative of LA occurrence.